IMPLEMENTASI PEMBELAJARAN DENGAN METODE MOORE TERMODIFIKASI UNTUK MENINGKATKAN KEMAMPUAN PEMBUKTIAN MATEMATIK MAHASISWA - abdul aziz saefudin (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This research aims to describe the improvement of student’s mathematical proving ability applying modified Moore method and conventional learning model in the subject of Algebra Structure. This research is a quasi-experimental research design using a nonequivalent control group design and used purposive sampling is as much as 41 students. The technique of collecting data used the mathematical proving ability test. Data were analyzed using two-step statistical descriptive and inferential statistical analysis. The research findings show that: 1) the mathematical proving ability of students who applying the Moore modified method significantly better than that students of applying the conventional learning model. 2) the improvement of the mathematical proving ability student that applying the Moore modified method of learning with a significantly better and more evenly than that students applying the conventional learning model. Based on these research, it can be recommended that learning algebra structure with modified Moore method can as an alternative method of learning to improve the mathematical proving ability.